Epidemiological profile and anatomopathological changes of biopsies of left kidneys from seven dogs affected by Dioctophyme renale in right kidney (Research, Society and Development, 2021)
Dioctofimatosis is a disease caused by the nematode Dioctophyme renale, which occurs mostly in dogs and has predilection mostly for the right kidney and when penetrating the renal capsule, it causes destruction and atrophy of the renal parenchyma, and only one fibrous capsule of the affected kidney may remain. Thus, seeking to establish the histological conditions of the contralateral kidney (RCL) of the affected animals, the objective of this study was to describe the epidemiological profile and anatomopathological changes found in left kidney biopsies of seven dogs undergoing nephrectomy due to Dioctophyme renale parasitism in right kidney. Information relative to race, sex, age range, medical history, histological changes, was tabbed and evaluated. For the biopsies were used incisional method. Of the 10 samples, 7 biopsy samples, collected by the incisional technique, were satisfactory for the study. Microscopically there were three cases (3/7) with membranous glomerulonephritis, four (4/7) had inflammatory infiltrate of mononucleated cells and focal fibrosis in two analyzed samples (2/7). In one case (1/7) focal segmental glomerulosclerosis was observed and one sample didn’t show any histological changes. It may have more than one change in one sample. The changes found in the biopsies indicate some impairment of the remaining kidney and suggesting that there maybe systemic, or at least inter-renal, action of the esophageal enzymes produced by the parasite. This study hopes to contribute to the staging of the renal functions of the remaining kidney and assist in the establishment of treatment in each case.